THE ROLE AND DEVELOPMENT OF ONLINE TOURISM IN THE WORLD AND IN UZBEKISTAN (Uzbek Scholar Journal, 2022)
This article is about creating convenience for tourists in the world and in Uzbekistan through the use of IT in tourism.